Determinan Status Kesehatan Balita di Provinsi Nusa Tenggara Timur Tahun 2019 - Muh. Reza Agung Wirawan; Siti Muchlisoh (Seminar Nasional Official Statistics, 2021)
Health is a fundamental right for every human being. Babies are the most vulnerable group of the population to have health problems. East Nusa Tenggara Province is one of provinces with low levels of babies’ health. Within three years, 2017-2019, the percentage of population aged 0-4 years who had health complaint increased from 47,69 percent in 2017 to 52,31 percent in 2019. The purpose of this research is to identify basic information about baby’s health status, to identify variables that affect baby’s health status and the tendency those variables to baby’s health status in Nusa Tenggara Timur Province in 2019. The data used in this research is raw data from National Socio-Economics Survey Housing and Health Module (Susenas MKP) in 2019 which is obtained from Badan Pusat Statistik. The analytical method used logistic binary regression. The results of research show that baby's age, mother's education level, mother's employment, mother’s health and sanitation access significantly affect baby’s health status. Babies who aged under two years, had mothers with education level are graduated high school or higher, employment, unhealthy and having bad sanitation access are riskier to get unhealthy.